ASSESSMENT OF LABOR RESOURCES OF SUBJECTS OF THE NORTH-CAUCASIAN FEDERAL DISTRICT UNDER CONDITIONS OF REGIONAL ASYMMETRY - E. A. Ostapenko (Вестник университета, 2020)
Disproportional development of territories is a common phenomenon. However, the natural asymmetry of regional socio-economic development is necessary, since it is it, that introduces dynamism into the economic and social justification of the allocation of labor resources and obtaining a positive effect from economic activity. In this regard, the main task of state authorities is to prevent particularly acute crisis socio-economic, environmental and other situations in certain territories as the basis for an abnormally high regional imbalance. Spatial imbalances based on the average annual number of employees of economic of the North Caucasian Federal District have been assessed in the article. The analysis of indicators of population employment has allowed us to reveal, that the differences in development trends and proportions between the regions are due to the typology of the regions, to determine the development trends of the regions and to evaluate spatial imbalances in certain types of economic activity.